2009
DOI: 10.1109/tns.2009.2033995
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Charge Collection Efficiency in Neutron Irradiated Silicon Detectors

Abstract: The charge collected from p-type silicon strip sensors irradiated to SuperLHC fluences has been determined with a beta source using fast front-end electronics. The bias voltage dependence of the collected charge and the hit detection efficiency have been measured before and after accelerated annealing. Predictions of the performance at the SuperLHC are derived

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The high atomic displacement threshold energy of 4H-SiC suggests enhanced irradiation hardness [13]. However, the measured radiation hardness proves inferior to comparable epitaxial p-on-n Si samples where the CCE reaches 67.7% at a neutron irradiation of 2.55 × 10 15 n eq /cm 2 , albeit measured at a temperature between −20 • C and −30 • C [29]. One reason might be the high impurity of the employed substrate, about two orders of magnitude higher than for typical Si tracking detectors.…”
Section: Discussionmentioning
confidence: 82%
“…The high atomic displacement threshold energy of 4H-SiC suggests enhanced irradiation hardness [13]. However, the measured radiation hardness proves inferior to comparable epitaxial p-on-n Si samples where the CCE reaches 67.7% at a neutron irradiation of 2.55 × 10 15 n eq /cm 2 , albeit measured at a temperature between −20 • C and −30 • C [29]. One reason might be the high impurity of the employed substrate, about two orders of magnitude higher than for typical Si tracking detectors.…”
Section: Discussionmentioning
confidence: 82%
“…The accumulation in more recent years of charge collection measurements from heavily irradiated silicon detectors has confirmed the larger than expected signal (see e.g. [3][4][5][6][7][8][9]). In particular, a number of results have been produced within the framework of the CERN-RD50 collaboration, dedicated to the development of radiation hard detectors for future super-collider applications [10].…”
Section: Introductionmentioning
confidence: 91%
“…Measurements at very high bias voltages have shown that charge multiplication phenomena [13]- [19] must be taken into account to understand the surprisingly good performance of heavily irradiated detectors. In addition to good charge collection efficiency (CCE) measured after "beneficial" annealing, CCE in n + -p type detectors is also less severely affected by long term reverse annealing than in the case of p + -n-type detectors [3,20,21]. Moreover, at sufficiently high bias voltages, significant increase of collected charge with reverse annealing was observed [20].…”
Section: Jinst 6 P11008mentioning
confidence: 99%
“…Pions will constitute a significant part of the radiation field in the upgraded LHC [1], the so called High Luminosity LHC (HL-LHC). Depending largely on the distance from the interaction point, they may contribute from less than 10% to displacement damage of the silicon strip detectors at largest radii rising up to ∼90% at inner layers of pixel detectors [2,3]. The remaining part of the damage will be caused by neutrons back-splashing from calorimeters and, to a lesser extent, protons.…”
Section: Introductionmentioning
confidence: 99%